Catalyzed process for dimerization of alkenes

JP2025026910APending Publication Date: 2025-02-26BASF SE
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2024197447
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2019-01-31
Filing Date
2024-11-12
Publication Date
2025-02-26

Smart Images

  • Figure 2025026910000001
    Figure 2025026910000001
  • Figure 2025026910000002
    Figure 2025026910000002
  • Figure 2025026910000003
    Figure 2025026910000003
Patent Text Reader

Abstract

To provide a process for the dimerization of alkenes which is economically advantageous and can be carried out with high yield and selectivity for dimerization products, particularly over an extended reaction time.SOLUTION: The present invention relates to a process for the dimerization of alkenes comprising: (1) providing a gas stream comprising one or more alkenes; and (2) contacting the gas stream provided in (1) with a catalyst for obtaining a mixture M1 comprising one or more dimerization products of the one or more alkenes, where the catalyst in (2) comprises a zeolitic material having a framework structure type selected from the group consisting of MOR, BEA, FER, MFI, TON, FAU, and mixtures of two or more thereof, where the framework structure of the zeolitic material comprises YO2, where Y stands for one or more tetravalent elements.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a catalytic process for the dimerization of alkenes, which uses a zeolitic material as a catalyst. [Background technology]

[0002] Alkene dimerization is an important reaction in the synthesis of higher molecular weight alkenes, especially highly branched products such as 2,4,4-trimethylpentene, the unsaturated precursor of 2,4,4-trimethylpentane (the reference compound with an "octane number" of 100 in the assignment of gasoline antiknock numbers). In the prior art, alkene dimerization is generally carried out using acidic resins and selectivity enhancers such as methanol and 2-butanol.

[0003] The disadvantages of the above-mentioned prior art methods include: - non-optimized selectivity, especially for the dimerization of alkenes to highly branched products, and - Use of selective enhancers Examples include:

[0004] Therefore, there is a need for an improved process for the dimerization of alkenes that can achieve high selectivity to highly branched products. Summary of the Invention [Problem to be solved by the invention]

[0005] It was therefore an object of the present invention to provide a process for the dimerization of alkenes which is economically advantageous and can be carried out with high yields and selectivities towards dimerization products, especially over long reaction times. Furthermore, it was an object of the present invention to provide a process for the dimerization of alkenes which shows high selectivity towards highly branched products. In addition to these, it was also an object of the present invention to provide a process for the dimerization of alkenes using a catalyst which can be regenerated in a time- and cost-effective manner without significant loss of catalytic performance even after multiple regeneration cycles. It was therefore surprisingly found that a process for the dimerization of alkenes which gives high selectivity towards dimerization products, especially towards highly branched dimerization products, can be provided by using a specific zeolitic material as catalyst. It was further unexpectedly found that the use of a zeolitic material not only makes it possible to maintain the dimerization reaction with high alkene conversion over long reaction times, but also that the zeolitic material can be easily regenerated and provides performance comparable to that of an unused catalyst even after multiple regeneration cycles. [Means for solving the problem]

[0006] The present invention therefore provides a process for the dimerization of alkenes comprising the steps of: (1) providing a gas stream comprising one or more alkenes; (2) contacting the gas stream provided in (1) with a catalyst to obtain a mixture M1 comprising one or more dimerization products of one or more alkenes; Including, (2) The catalyst in the present invention comprises a zeolite material having a framework structure type selected from the group consisting of MOR, BEA, FER, MFI, TON, FAU, and mixtures of two or more thereof; The framework structure of the zeolitic material comprises YO2, where Y represents one or more tetravalent elements; It concerns the method. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0007] According to the present invention, it is preferred that the zeolitic material has a framework structure type selected from the group consisting of MOR, BEA, MFI and mixtures of two or three of these, more preferably the zeolitic material has a MOR and / or BEA type framework structure, more preferably a BEA type framework structure.

[0008] No particular restrictions apply with regard to the particular zeolites that may be included in the zeolitic material used in the process of the present invention, provided that the zeolitic material has a framework type selected from the group consisting of MOR, BEA, FER, MFI, TON, FAU, and mixtures of two or more thereof. Thus, by way of example, it is preferred according to the present invention that the zeolitic material comprises one or more zeolites selected from the group consisting of mordenite, zeolite beta, ferrierite, ZSM-5, ZSM-22, and zeolite Y, more preferably that the zeolitic material comprises one or more zeolites selected from the group consisting of mordenite, zeolite beta, and ZSM-5, more preferably that the zeolitic material comprised in the catalyst comprises mordenite and / or zeolite beta, more preferably zeolite beta, more preferably that the zeolitic material comprised in the catalyst is mordenite and / or zeolite beta, more preferably zeolite beta.

[0009] Regarding the ions contained in the ion exchange sites of the zeolite material, no particular limitation is applied according to the present invention, and the zeolite material is preferably a zeolite material having H in the ion exchange sites of the zeolite framework. + and more preferably the zeolitic material is in the H form.

[0010] According to the present invention, the zeolite material contained in the catalyst contains 5% by mass or less of metal M calculated as the element and based on 100% by mass of YO2 contained in the framework structure of the zeolite material, and preferably 1% by mass or less, more preferably 0.5% by mass or less, more preferably 0.1% by mass or less, more preferably 0.05% by mass or less, more preferably 0.01% by mass or less, more preferably 0.005% by mass or less, more preferably 0.001% by mass or less, more preferably 0.0005% by mass or less, and more preferably 0.0001% by mass or less, calculated as the element and based on 100% by mass of YO2 contained in the framework structure of the zeolite material; It is preferred that the metal M represents Na, preferably Na and K, more preferably the alkali metals and more preferably the alkali and alkaline earth metals.

[0011] In principle, there are no limitations as to the elements or compounds that may be contained in the zeolitic material. However, according to the present invention, it is preferred that the zeolitic material contained in the catalyst contains no more than 5% by weight of phosphorus, calculated as element and relative to 100% by weight of YO2 contained in the framework structure of the zeolitic material, and more preferably no more than 1% by weight, more preferably no more than 0.5% by weight, more preferably no more than 0.1% by weight, more preferably no more than 0.05% by weight, more preferably no more than 0.01% by weight, more preferably no more than 0.005% by weight, more preferably no more than 0.001% by weight, more preferably no more than 0.0005% by weight and more preferably no more than 0.0001% by weight, calculated as element and relative to 100% by weight of YO2 contained in the framework structure of the zeolitic material.

[0012] With regard to the ions that may be contained in the ion-exchange sites of the zeolitic material, according to the present invention, the zeolitic material comprises one or more metal cations in the ion-exchange sites of the zeolitic framework, the one or more metal cations being selected from the group consisting of alkaline earth metals and rare earth metals, preferably including mixtures of two or more of these, preferably from the group consisting of Mg, Ca, Sr, Sc, Y, La, Ce, Pr, Nd, and mixtures of two or more of these, more preferably from the group consisting of Mg, Ca, La, Ce, and mixtures of two or more of these, and more preferably the zeolitic material comprises one or more metal cations in the ion-exchange sites of the zeolitic framework, the one or more metal cations being selected from the group consisting of alkaline earth metals and rare earth metals, preferably including mixtures of two or more of these, more preferably from the group consisting of Mg, Ca, La, Ce, and mixtures of two or more of these, It is preferred that the zeolitic material comprises one or more zeolites selected from the group consisting of Mg-ZSM-5, La-ZSM-5, La-mordenite, and mixtures of two or three thereof, more preferably La-ZSM-5 and / or La-mordenite, more preferably that the zeolitic material is composed of one or more zeolites selected from the group consisting of Mg-ZSM-5, La-ZSM-5, La-mordenite, and mixtures of two or three thereof, more preferably that the zeolitic material is La-ZSM-5 and / or La-mordenite.

[0013] According to the present invention, it is preferred that the one or more tetravalent elements contained in the framework structure of the zeolitic material may be any suitable tetravalent element, wherein Y is selected from the group consisting of Si, Sn, Ti, Zr, Ge, and mixtures of two or more thereof, more preferably from the group consisting of Si, Sn, Ti, and mixtures of two or more thereof, Y preferably comprises Si or both Si and Sn, more preferably Y comprises Si, more preferably Y is either Si or both Si and Sn, more preferably Y is Si, more preferably the zeolitic material comprises a zeolite beta having a framework comprising Si and Sn as tetravalent elements, more preferably a zeolite beta having a framework comprising Si and Sn as tetravalent elements, more preferably the zeolitic material is composed of a zeolite beta having a framework comprising Si and Sn as tetravalent elements, more preferably a zeolite beta having a framework comprising Si and Sn as tetravalent elements.

[0014] According to the present invention, it is further preferred that the framework structure of the zeolitic material further comprises X2O3, wherein X represents one or more trivalent elements, X being selected from the group consisting of Al, B, In, Ga, and mixtures of two or more thereof, preferably X comprises Al, more preferably X is Al.

[0015] According to certain and preferred embodiments of the present invention, in which the framework structure of the zeolitic material further comprises X2O3, it is preferred that the zeolitic material exhibits a molar ratio of YO2:X2O3 in the range of 2-300, more preferably 6-200, more preferably 8-150, more preferably 10-100, more preferably 15-80, more preferably 20-70, more preferably 40-60, and more preferably 45-55.

[0016] According to particular and preferred embodiments of the present invention, in which the framework structure of the zeolitic material further comprises X2O3, it is preferred that the zeolitic material comprises ZSM-5, more preferably the zeolitic material is ZSM-5.

[0017] Preferably, the zeolitic material contained in the catalyst has a total amount of acid sites in the range of 0.4-4 mmol / g, preferably 0.5-3 mmol / g, more preferably 0.6-2.8 mmol / g, more preferably 0.8-2.6 mmol / g, more preferably 1-2.4 mmol / g, more preferably 1.2-2.2 mmol / g, more preferably 1.4-2 mmol / g, more preferably 1.6-1.9 mmol / g, and more preferably 1.7-1.8 mmol / g, where the total amount of acid sites is defined as the total molar amount of ammonia desorbed per mass of the zeolitic material as measured by temperature programmed desorption of ammonia (NH3-TPD).

[0018] Regarding the total amount of acid sites of the zeolite material contained in the catalyst, according to the present invention, the total amount of acid sites is preferably defined as the amount of ammonia desorbed per mass of the zeolite material, measured by temperature programmed desorption of ammonia (NH3-TPD) in a temperature range of 150 to 750°C, preferably 180 to 680°C, more preferably 190 to 630°C, more preferably 200 to 600°C, more preferably 205 to 570°C, more preferably 210 to 540°C, more preferably 215 to 490°C, and more preferably 220 to 440°C.

[0019] Regarding the acid sites of the zeolite material contained in the catalyst, there is no particular limitation as to how many acid sites are weak, medium, and / or strong. However, according to the present invention, it is preferred that the zeolite material contained in the catalyst has a certain amount of medium acid sites, and the amount of medium acid sites is in the range of 0.4 to 4 mmol / g, preferably 0.5 to 3 mmol / g, more preferably 0.6 to 2.8 mmol / g, more preferably 0.8 to 2.6 mmol / g, more preferably 1 to 2.4 mmol / g, more preferably 1.2 to 2.2 mmol / g, more preferably 1.4 to 2 mmol / g, more preferably 1.6 to 1.9 mmol / g, and more preferably 1.7 to 1.8 mmol / g. Regarding the amount of intermediate acid sites contained in the zeolite material contained in the catalyst, according to the present invention, the amount of intermediate acid sites is preferably defined as the amount of ammonia desorbed per mass of the zeolite material measured by temperature programmed desorption of ammonia (NH3-TPD) in a temperature range of 150 to 400°C, preferably 180 to 320°C, more preferably 190 to 280°C, more preferably 200 to 250°C, more preferably 205 to 240°C, more preferably 210 to 230°C, and more preferably 215 to 220°C.

[0020] According to the present invention, the amount of strong acid sites (strong acid sites) of the zeolite material contained in the catalyst is also not particularly limited, but it is preferable that the zeolite material contained in the catalyst has strong acid sites of less than 1 mmol / g, more preferably less than 0.5 mmol / g, more preferably less than 0.2 mmol / g, more preferably less than 0.1 mmol / g, more preferably less than 0.05 mmol / g, more preferably less than 0.03 mmol / g, more preferably less than 0.02 mmol / g, more preferably less than 0.01 mmol / g, more preferably less than 0.005 mmol / g, and more preferably less than 0.001 mmol / g. Regarding the amount of strong acid sites contained in the zeolite material contained in the catalyst, according to the present invention, the amount of strong acid sites is preferably defined as the amount of ammonia desorbed per mass of the zeolite material measured by temperature programmed desorption of ammonia (NH3-TPD) in a temperature range of 300 to 750°C, preferably 400 to 720°C, more preferably 450 to 690°C, more preferably 500 to 670°C, more preferably 530 to 650°C, more preferably 550 to 630°C, more preferably 570 to 610°C, and more preferably 590 to 600°C.

[0021] The total amount of acid sites, the amount of medium acid sites and the amount of strong acid sites as used herein can be easily measured by known methods, preferably by temperature programmed desorption of ammonia (NH3-TPD), preferably using an automatic chemisorption analyzer with a thermal conductivity detector, preferably by continuous analysis of the desorbed species by an online mass spectrometer, preferably the temperature is measured by a Ni / Cr / Ni thermocouple directly above the sample in a quartz tube, more preferably the online mass spectrometer monitors the desorption of ammonia by using the molecular weight of ammonia 16, more preferably the automatic chemisorption analyzer is an AutoChem II 2920 from Micromeritics, more preferably the online mass spectrometer is an OmniStar QMG200 from Pfeiffer Vacuum. Preferably, the measurement includes steps 1. preparation, 2. saturation with NH3, 3. removal of excess ammonia, and 4. NH3-TPD, more preferably the 4. NH3-TPD step for the total amount of acid sites includes heating to 600°C under He flow, preferably at a heating rate of 10K / min, and then preferably holding the temperature at 600°C for 30 minutes. To measure the amount of medium acid sites, the 4. NH3-TPD step is more preferably carried out in a temperature range of 250°C to 500°C. To measure the amount of strong acid sites, the 4. NH3-TPD step is more preferably carried out in a temperature range of more than 500°C. According to the present invention, it is more preferable that the total amount of acid sites as well as the amount of medium acid sites and the amount of strong acid sites used herein are measured according to the method described herein in the example under "measurement of acid sites".

[0022] Preferably, the one or more alkenes provided in (1) are of formula (I)

[0023] [ka]

[0024] (wherein R and R' are alkyl groups). The alkenes include one or more alkenes according to the formula:

[0025] Further, according to the process of the present invention, one or more dimerization products of one or more alkenes obtained in (2) are represented by the formula (II):

[0026] [ka]

[0027] where R and R' are again alkyl groups. It is preferred that the alkene comprises one or more alkenes according to the formula:

[0028] With regard to the alkyl groups R and R', according to the method of the present invention, it is preferred that R and R' are, independently of each other, optionally branched and / or optionally substituted and / or optionally unsaturated C1-C6 alkyl groups, preferably C1-C5 alkyl groups, more preferably C1-C4 alkyl groups, more preferably C1-C3 alkyl groups, more preferably C1-C2 alkyl groups, and more preferably C1 alkyl groups, which may be optionally branched and / or optionally substituted and / or optionally unsaturated, selected from the group consisting of C1-C6 alkyl groups, preferably C1-C5 alkyl groups, more preferably C1-C4 alkyl groups, more preferably C1-C3 alkyl groups, more preferably C1-C2 alkyl groups, and more preferably C1 alkyl groups; more preferably R and R' are, independently of each other, selected from the group consisting of optionally substituted methyl, ethyl, propyl, butyl, pentyl, and hexyl, more preferably from the group consisting of optionally substituted methyl, ethyl, propyl, butyl, and pentyl, more preferably from the group consisting of optionally substituted methyl, ethyl, propyl, and butyl, more preferably from the group consisting of optionally substituted methyl, ethyl, and propyl; more preferably R and R' are, independently of each other, optionally substituted methyl or ethyl, preferably methyl.

[0029] According to the process of the present invention, the one or more alkenes provided in (1) are therefore selected from the group consisting of optionally substituted isobutene, 2-methyl-1-butene, 2-ethyl-1-butene, 2-methyl-1-pentene, 2-ethyl-1-pentene, 2-n-propyl-1-pentene, 2,3-dimethyl-1-butene, 2-ethyl-3-methyl-1-butene, 2-i-propyl-1-pentene, 2-i-propyl-3-methyl-1-butene, and mixtures of two or more thereof, more preferably optionally substituted isobutene, 2-methyl-1-butene, 2-ethyl-1-butene, 2-methyl-1-pentene, 2-ethyl Preferably, the alkene of formula (II) comprises one or more alkenes selected from the group consisting of optionally substituted isobutene, 2-methyl-1-butene, 2-ethyl-1-butene, 2-ethyl-3-methyl-1-butene, and mixtures of two or more thereof, more preferably selected from the group consisting of optionally substituted isobutene, 2-methyl-1-butene, 2-ethyl-1-butene, 2-methyl-1-pentene, 2,3-dimethyl-1-butene, and mixtures of two or more thereof, more preferably the alkene of formula (II) is optionally substituted isobutene and / or 2-methyl-1-butene, preferably isobutene or 2-methyl-1-butene and more preferably isobutene.

[0030] According to the process of the present invention, the one or more dimerization products obtained in (2) comprise one or more alkanes and / or one or more alkenes, preferably one or more alkenes, more preferably one or more C4-C20 alkenes, more preferably one or more C4-C16 alkenes, more preferably one or more C5-C14 alkenes, more preferably one or more C5-C13 alkenes, more preferably one or more C6-C12 alkenes, more preferably one or more C6-C11 alkenes, more preferably one or more C7-C10 alkenes, more preferably one or more C7-C9 alkenes, more preferably one or more C8 alkenes, more preferably the one or more dimerization products obtained in (2) comprise one or more alkenes selected from the group consisting of 1-octene, 2,4,4-trimethyl-1-pentene, 2,4,4-trimethyl-2-pentene, and mixtures of two or three thereof, more preferably It is preferred that the one or more dimerization products obtained in (2) comprise 1-octene and / or 2,4,4-trimethyl-1-pentene, more preferably 2,4,4-trimethyl-1-pentene.

[0031] With regard to the amount of alkenes contained in the gas stream supplied in (1), no particular limitations apply according to the process of the present invention, and it is preferred that the content of one or more alkenes in the gas stream supplied in (1) and contacted with the catalyst in (2) is in the range of 5 to 100 vol.%, more preferably in the range of 10 to 99 vol.%, more preferably in the range of 15 to 98 vol.%, more preferably in the range of 20 to 95 vol.%, more preferably in the range of 25 to 90 vol.%, more preferably in the range of 30 to 80 vol.%, more preferably in the range of 35 to 70 vol.%, more preferably in the range of 40 to 60 vol.%, and more preferably in the range of 45 to 55 vol.%, based on the total volume of the gas stream.

[0032] As to the compounds that may be contained in the gas stream supplied in (1), no particular restrictions are applied according to the present invention, but it is preferred that the gas stream supplied in (1) and contacted with the catalyst in (2) contains no more than 50 vol.%, more preferably no more than 30 vol.%, more preferably no more than 20 vol.%, more preferably no more than 10 vol.%, more preferably no more than 5 vol.%, more preferably no more than 3 vol.%, more preferably no more than 2 vol.%, more preferably no more than 1 vol.%, more preferably no more than 0.5 vol.%, more preferably no more than 0.1 vol.%, more preferably no more than 0.05 vol.%, more preferably no more than 0.01 vol.%, more preferably no more than 0.005 vol.%, and more preferably no more than 0.001 vol.% of aliphatic organic compounds based on the total volume of the gas stream. According to the present invention, it is preferred that the one or more aliphatic organic compounds are selected from the group consisting of optionally substituted and / or optionally cyclic and / or optionally branched (C2-C20) hydrocarbons and mixtures of two or more thereof, preferably (C2-C16) hydrocarbons, more preferably (C2-C16) hydrocarbons, more preferably (C2-C14) hydrocarbons, more preferably (C2-C12) hydrocarbons, more preferably (C2-C10) hydrocarbons, more preferably (C2-C8) hydrocarbons, more preferably (C2-C6) hydrocarbons, more preferably (C3-C5) hydrocarbons, and more preferably C4 hydrocarbons, and mixtures thereof. With regard to the optionally substituted and / or optionally branched hydrocarbons, it is preferred that the one or more optionally substituted and / or optionally cyclic hydrocarbons are branched, more preferably the one or more branched hydrocarbons are of the formula:

[0033] [ka]

[0034] (In the formula, R 1 , R 2 , and R 3are each independently an optionally substituted and / or optionally cyclic and / or optionally branched (C1-C8) alkyl, preferably a (C1-C6) alkyl, more preferably a (C1-C5) alkyl, more preferably R 1 , R 2 , and R 3 are each independently an optionally substituted and / or optionally branched (C1-C4) alkyl, preferably a (C1-C3) alkyl, more preferably R 1 , R 2 , and R 3 are each independently optionally substituted methyl or ethyl, preferably optionally substituted methyl. It is preferred that the compound has the formula:

[0035] With regard to the optional substitution of the one or more aliphatic organic compounds, the one or more aliphatic organic compounds are substituted with one or more functional groups, the one or more functional groups being selected from the group consisting of hydroxyl, halogen, carbonyl, aldehyde, carbonate, carboxylate, carboxyl, ester, ether, carboxamide, amine, imine, cyanate, isocyanate, nitrate, nitrile, isonitrile, sulfide, sulfinyl, sulfonyl, sulfino, sulfo, thiocyanate, isothiocyanate, phosphino, phosphono, and phosphate, more preferably hydroxyl, halogen, carbonyl, aldehyde, carboxylate, carboxyl, ester, ether, carboxamide, amine, imine, cyanate, isocyanate, nitrate, nitrile, isonitrile, and combinations of two or more thereof. more preferably selected from the group consisting of hydroxyl, halogen, carbonyl, aldehyde, carboxylate, carboxyl, ester, ether, and a combination of two or more thereof; more preferably selected from the group consisting of hydroxyl, halogen, carbonyl, alkoxy, and a combination of two or more thereof; more preferably selected from the group consisting of hydroxyl, fluoro, chloro, bromo, (C1-C3)alkoxy, and a combination of two or more thereof; more preferably selected from the group consisting of hydroxyl, fluoro, chloro, (C1-C2)alkoxy, and a combination of two or more thereof; more preferably selected from the group consisting of hydroxyl, fluoro, chloro, methoxy, and a combination of two or more thereof, and more preferably selected from the group consisting of one or more aliphatic compounds substituted with one or more hydroxyl groups.

[0036] However, in accordance with the present invention, it is alternatively preferred that the one or more aliphatic organic compounds are unsubstituted hydrocarbons, more preferably that the one or more aliphatic organic compounds comprise isobutane, more preferably that the one or more aliphatic organic compounds are isobutane.

[0037] However, it is preferred that the gas stream provided in (1) and contacted with the catalyst in (2) further comprises one or more inert gases, the one or more inert gases being selected from the group consisting of nitrogen, helium, argon, CO2, and mixtures of two or more thereof, preferably from the group consisting of nitrogen, argon, CO2, and mixtures of two or more thereof, more preferably the gas stream further comprises nitrogen and / or argon, more preferably nitrogen and argon. With regard to the content, it is preferred that the content of one or more inert gases in the gas stream provided in (1) and contacted with the catalyst in (2) is in the range of 0-95% by volume, preferably in the range of 1-90% by volume, more preferably in the range of 2-85% by volume, more preferably in the range of 5-80% by volume, more preferably in the range of 10-75% by volume, more preferably in the range of 20-70% by volume, more preferably in the range of 30-65% by volume, more preferably in the range of 40-60% by volume, and more preferably in the range of 45-55% by volume, based on the total volume of the gas stream.

[0038] According to the method of the present invention, the contact in (2) is preferably carried out at a temperature in the range of 80 to 350°C, more preferably 100 to 320°C, more preferably 120 to 300°C, more preferably 140 to 280°C, more preferably 160 to 260°C, more preferably 180 to 250°C, more preferably 200 to 245°C, more preferably 220 to 240°C, and more preferably 225 to 235°C.

[0039] Additionally and independently, it is preferred that the contacting in (2) is carried out at a pressure in the range of 2 to 80 bar, preferably 4 to 60 bar, more preferably 6 to 50 bar, more preferably 8 to 45 bar, more preferably 10 to 40 bar, more preferably 12 to 38 bar, more preferably 14 to 36 bar, more preferably 16 to 34 bar, more preferably 18 to 32 bar, more preferably 20 to 30 bar, more preferably 22 to 28 bar, and more preferably 24 to 26 bar.

[0040] In principle, the process of the invention can be carried out in continuous and / or batch mode, such that the contacting in (2) is preferably carried out in continuous and / or batch mode, preferably in continuous mode.

[0041] For specific and preferred embodiments of the process of the present invention carried out in a continuous mode, the space velocity of the contact in (2) is from 10 to 10,000 h -1 , preferably 50 to 5,000 hours -1 , more preferably 100 to 3,000 hours -1 , more preferably 300 to 2,500 hours -1 , more preferably 500 to 1,800 hours -1 , more preferably 700 to 1,500 hours -1 , more preferably 800 to 1,200 hours -1 , more preferably 900 to 1,100 hours -1 Additionally and independently, when the contacting in (2) is carried out in a continuous manner, it is preferred that the catalyst lifetime is in the range of 50 to 2,000 hours, preferably 100 to 1,000 hours, more preferably 150 to 500 hours, more preferably 200 to 400 hours, more preferably 230 to 350 hours, and more preferably 250 to 300 hours, during which the dimerization reaction is carried out in a continuous manner without interruption.

[0042] The method of the present invention comprises: (3) separating one or more unreacted alkenes from the reaction mixture M1 obtained in (2) to obtain a mixture M2 containing one or more alkenes; (4) recycling the mixture M2 containing one or more alkenes to (1); It is preferred that the compound further comprises:

[0043] Additionally and independently, according to the process of the present invention, it is preferred that the catalyst is regenerated at regular intervals. With regard to catalyst regeneration, it is preferred that the regeneration is carried out by contacting the catalyst with a gas stream containing oxygen, the contacting being carried out at a temperature in the range of 250-1000°C, preferably 300-900°C, more preferably 350-800°C, more preferably 400-700°C, more preferably 450-650°C, and more preferably 500-600°C. Additionally and independently, it is preferred that the regeneration gas stream contains oxygen in an amount of 0.1-25% by volume, preferably 0.5-20% by volume, more preferably 1-15% by volume, more preferably 1.5-12% by volume, more preferably 2-10% by volume, more preferably 2.5-8% by volume, more preferably 3-7% by volume, more preferably 3.5-6% by volume, and more preferably 4-5% by volume, based on the total volume of the gas stream. With regard to the regeneration gas stream, it is preferred that the gas stream further comprises one or more inert gases, the one or more inert gases being selected from the group consisting of nitrogen, helium, argon, CO2 and mixtures of two or more thereof, preferably from the group consisting of nitrogen, argon, CO2 and mixtures of two or more thereof, more preferably the gas stream further comprises nitrogen and / or argon, more preferably nitrogen and argon. With regard to the content of one or more inert gases in the regeneration gas stream, according to the method of the present invention, it is preferred that the content is in the range of 75-99.9% by volume, preferably in the range of 80-99.5% by volume, more preferably in the range of 85-99% by volume, more preferably in the range of 88-98.5% by volume, more preferably in the range of 90-98% by volume, more preferably in the range of 92-97.5% by volume, more preferably in the range of 93-97% by volume, more preferably in the range of 94-96.5% by volume, and more preferably in the range of 95-96% by volume, based on the total volume of the gas stream.

[0044] With regard to the zeolitic material contained in the catalyst, according to the method of the present invention, when the zeolitic material contained in the catalyst has a framework structure type BEA, the zeolitic material has at least the following reflections:

[0045] [Table 1]

[0046] wherein 100% is associated with the maximum peak intensity in the 20-45°2θ range of the X-ray powder diffraction pattern, and the BEA-type framework structure preferably comprises YO2 and X2O3, Y being a tetravalent element and X being a trivalent element. According to said specific and preferred embodiments, it is preferred that the zeolitic material having a BEA-type framework structure exhibits a molar ratio of YO2:X2O3 in the range of 2-100, preferably 3-50, more preferably 4-30, more preferably 5-25, more preferably 6-20, more preferably 7-18, more preferably 8-16, and more preferably 9-14. Furthermore and independently, it is preferred that the zeolitic material comprises zeolite beta, preferably the zeolitic material is zeolite beta. Furthermore and independently, it is preferred that the zeolitic material having a BEA-type framework structure contained in the catalyst is obtainable and / or obtained by an organotemplate-free synthetic process.

[0047] According to the present invention, the terms "organic template" and "organic structure directing agent" are used synonymously, the term "organic template" or "organic structure directing agent" refers to any organic compound, preferably any organic compound containing an organic cation, that can be added to a synthesis process for the preparation of a zeolitic material having a BEA framework structure as a structure directing agent. Furthermore, the term "organic template-free" as used in the present application refers to a synthesis method that does not use an organic template as a structure directing agent, i.e. is organic template-free, and defines a synthesis method for the preparation of a zeolitic material having a BEA framework structure, in which the reaction mixture at any point in the process does not contain more than 1% by weight of organic structure directing agent relative to 100% by weight of YO2 contained in the reaction mixture, preferably more than 0.5% by weight, more preferably more than 0.1% by weight, more preferably more than 0.05% by weight, more preferably more than 0.01% by weight, more preferably more than 0.005% by weight, more preferably more than 0.001% by weight, more preferably more than 0.0005% by weight, and more preferably more than 0.0001% by weight of organic structure directing agent relative to 100% by weight of YO2 contained in the reaction mixture.

[0048] For the zeolitic material with a BEA-type framework structure used in the method of the invention, no particular restrictions apply to the method of obtaining X-ray diffraction to measure the diffraction angle and reflection intensity, except that Cu K (alpha 1) radiation is used to this effect. However, according to the method of the invention, it is preferred that the X-ray diffraction pattern is obtained from an X-ray diffraction experiment of the powder material carried out using a D8 Advance X-ray diffractometer (Bruker AXS) equipped with a Lynx Eye detector, using Cu K alpha-1 radiation, Cu-Ka radiation is used in Bragg-Brentano geometry, and data is collected from 2 to 50° (2θ) using a step size of 0.02° and a dwell time of 2.4 seconds per step. Furthermore, it is preferred that the parameters used in the X-ray diffraction experiment are as follows: Primary side: ASS with divergence slit 0.1° Secondary side: 0.1 fixed slit Detector: Lynx Eye, 3°.

[0049] Regarding the preferred organic template-free synthesis method for obtaining zeolitic materials having a BEA-type framework structure, according to the present invention, the organic template-free synthesis method comprises the steps of: (A) preparing a mixture comprising one or more YO2 sources, one or more X2O3 sources, and seed crystals, the seed crystals comprising a material having a BEA-type framework structure; (B) crystallizing the mixture obtained in (A) to obtain a zeolitic material having a BEA-type framework structure; Including, Y is a tetravalent element and X is a trivalent element; It is preferred that the mixture prepared in (A) and crystallized in (B) does not contain an organic template as a structure directing agent.

[0050] Preferably, the mixture prepared in (A) and crystallized in (B) contains no more than 5% by weight of carbon, calculated as the element and relative to 100% by weight of Y contained in the mixture, preferably no more than 1% by weight, more preferably no more than 0.5% by weight, more preferably no more than 0.1% by weight, more preferably no more than 0.05% by weight, more preferably no more than 0.01% by weight, more preferably no more than 0.005% by weight, more preferably no more than 0.001% by weight, more preferably no more than 0.0005% by weight, and more preferably no more than 0.0001% by weight.

[0051] With regard to the zeolitic material having a BEA-type framework structure obtained in (B), the zeolitic material contains one or more alkali metals AM, the AM being preferably selected from the group consisting of Li, Na, K, Cs, and combinations of two or more thereof, more preferably from the group consisting of Li, Na, K, and combinations of two or more thereof, and more preferably the alkali metal AM is Na and / or K, more preferably Na. Furthermore, it is preferred that the molar ratio of AM:YO2 in the mixture prepared in (A) and crystallized in (B) is in the range of 0.05-5, preferably 0.1-2, more preferably 0.3-1, more preferably 0.4-0.8, more preferably 0.45-0.7, more preferably 0.5-0.65, and more preferably 0.55-0.6.

[0052] For the preferred organic template-free synthesis method that results in a zeolitic material with a BEA-type framework structure, it is preferred that Y is selected from the group consisting of Si, Sn, Ti, Zr, Ge, and a mixture of two or more thereof, and Y is preferably Si. Furthermore, it is preferred that the one or more YO2 sources contained in the mixture prepared in (A) and crystallized in (B) comprise one or more silicates, preferably one or more alkali metal silicates, and the alkali metal is preferably selected from the group consisting of Li, Na, K, Rb, and Cs, more preferably the alkali metal is Na and / or K, more preferably the alkali metal is Na, and more preferably the one or more YO2 sources contained in the mixture prepared in (A) and crystallized in (B) comprise water glass, preferably sodium silicate and / or potassium silicate, more preferably sodium silicate. Furthermore, it is preferred that the one or more YO2 sources contained in the mixture prepared in (A) and crystallized in (B) further comprise one or more silicas, preferably one or more silica hydrosols and / or one or more colloidal silicas, and more preferably one or more colloidal silicas.

[0053] With regard to the preferred organic template-free synthesis method resulting in a zeolitic material having a BEA-type framework structure, it is preferred that X is selected from the group consisting of Al, B, In, Ga, and mixtures of two or more thereof, preferably X is Al. According to the above specific and preferred embodiments, the one or more X2O3 sources contained in the mixture prepared in (A) and crystallized in (B) comprise one or more aluminates, preferably alkali metal aluminates, the alkali metal being preferably selected from the group consisting of Li, Na, K, Rb, and Cs, more preferably the alkali metal being Na and / or K, more preferably the alkali metal being Na. Furthermore and independently, it is preferred that the YO2:X2O3 molar ratio of the mixture prepared in (A) and crystallized in (B) is in the range of 1-200, preferably 5-100, more preferably 10-50, more preferably 15-40, more preferably 20-30, more preferably 23-25, and more preferably 23.5-24.

[0054] With regard to the preferred organic template-free synthesis method resulting in a zeolitic material having a BEA-type framework structure, it is further preferred that the amount of seed crystals contained in the mixture prepared in (A) and crystallized in (B) is in the range of 0.5-30 wt%, preferably 1-25 wt%, more preferably 3-20 wt%, more preferably 5-15 wt%, more preferably 8-12 wt%, and more preferably 9-11 wt%, calculated as YO2, relative to 100 wt% of the YO2 source or sources in the mixture. Additionally and independently, it is preferred that the mixture prepared in (A) and crystallized in (B) further comprises one or more solvents, said one or more solvents preferably comprising water, more preferably deionized water, and more preferably water, preferably deionized water, is used as the solvent further contained in the mixture prepared in (A) and crystallized in (B). For certain and preferred embodiments, when the one or more solvents comprise water, it is preferred that the HO:YO molar ratio of the mixture prepared in (A) and crystallized in (B) ranges from 5 to 100, preferably from 10 to 50, more preferably from 13 to 30, more preferably from 15 to 20, and more preferably from 17 to 18.

[0055] With regard to the preferred organotemplate-free synthesis process leading to a zeolitic material having a BEA-type framework structure, it is further preferred that the crystallization in (B) comprises heating the mixture at a temperature in the range of preferably 80-200° C., more preferably 90-180° C., more preferably 100-160° C., more preferably 110-140° C., and more preferably 115-130° C. According to said specific and preferred embodiments, it is preferred that the crystallization in (B) is carried out under autogenous pressure, preferably under solvothermal conditions and more preferably under hydrothermal conditions.

[0056] For the preferred organotemplate-free synthesis method to obtain zeolitic materials having a BEA-type framework structure, it is preferred that in (B) the mixture is heated for a period in the range of 5 to 200 hours, preferably 20 to 150 hours, more preferably 50 to 100 hours, and more preferably 65 to 75 hours.

[0057] An organic template-free synthesis method for obtaining zeolitic materials having a BEA-type framework structure is provided, (C) isolating the zeolitic material having a BEA-type framework structure obtained in (B), preferably by filtration; and (D) optionally washing the zeolitic material with a BEA-type framework structure obtained in (B) or (C), preferably in (C); and / or (E) Optionally, drying the zeolitic material having a BEA-type framework structure obtained in (B), (C) or (D), preferably in (D). Further comprising: Steps (C) and / or (D) and / or (E) may be performed in any order; Preferably, one or more of the above steps are repeated, preferably one or more times.

[0058] Independently, an organic template-free synthesis method for obtaining zeolitic materials with BEA-type framework structures is disclosed, (F) One or more of the ionic non-framework elements contained in the zeolitic material having a BEA-type framework structure obtained in (C), (D) or (E), preferably (E), is ionized with H + and / or NH4 + , preferably NH4 + and / or preferably and (G) drying and / or calcining, preferably drying and calcining, the zeolitic material having a BEA-type framework structure obtained in (C), (D), (E) or (F). It is preferred that the compound further comprises:

[0059] The present invention is further illustrated by the following set of embodiments and combinations of the embodiments with the indicated dependencies and back references. In particular, it should be noted that in each case where a range of embodiments is mentioned, in the context of a term such as "the method according to any one of embodiments 1 to 4", it is meant that all embodiments within this range are clearly disclosed for those skilled in the art, that is, the expression of this term should be understood by those skilled in the art to be equivalent to "the method according to any one of embodiments 1, 2, 3, and 4".

[0060] 1. A process for the dimerization of alkenes comprising the steps of: (1) providing a gas stream comprising one or more alkenes; (2) contacting the gas stream provided in (1) with a catalyst to obtain a mixture M1 comprising one or more dimerization products of one or more alkenes; Including, (2) The catalyst in the present invention comprises a zeolite material having a framework structure type selected from the group consisting of MOR, BEA, FER, MFI, TON, FAU, and mixtures of two or more thereof; The framework structure of the zeolitic material comprises YO2, where Y represents one or more tetravalent elements; method.

[0061] 2. The method according to embodiment 1, wherein the zeolitic material has a framework structure type selected from the group consisting of MOR, BEA, MFI, and mixtures of two or three thereof, preferably the zeolitic material has a MOR and / or BEA type framework structure, more preferably a BEA type framework structure.

[0062] 3. The method according to embodiment 1 or 2, wherein the zeolitic material comprises one or more zeolites selected from the group consisting of mordenite, zeolite beta, ferrierite, ZSM-5, ZSM-22 and zeolite Y, preferably from the group consisting of mordenite, zeolite beta and ZSM-5, more preferably the zeolitic material comprised in the catalyst comprises mordenite and / or zeolite beta, more preferably zeolite beta, more preferably the zeolitic material comprised in the catalyst is mordenite and / or zeolite beta, more preferably zeolite beta.

[0063] 4. Zeolite materials are charged with H at the ion exchange sites of the zeolite framework. + 4. The method according to any one of the preceding embodiments, wherein the zeolitic material is in the H form.

[0064] 5. The zeolitic material contained in the catalyst contains 5% by weight or less of metal M, calculated as the element and based on 100% by weight of YO2 contained in the framework structure of the zeolitic material, preferably 1% by weight or less, more preferably 0.5% by weight or less, more preferably 0.1% by weight or less, more preferably 0.05% by weight or less, more preferably 0.01% by weight or less, more preferably 0.005% by weight or less, more preferably 0.001% by weight or less, more preferably 0.0005% by weight or less, and more preferably 0.0001% by weight or less, The method according to any one of the preceding embodiments, wherein the metal M represents Na, preferably Na and K, more preferably the alkali metals and more preferably the alkali and alkaline earth metals.

[0065] 6. The method of any one of embodiments 1 to 5, wherein the zeolitic material contained in the catalyst contains no more than 5% by weight phosphorus, calculated as element and based on 100% by weight YO2 contained in the framework structure of the zeolitic material, preferably no more than 1% by weight phosphorus, more preferably no more than 0.5% by weight, more preferably no more than 0.1% by weight, more preferably no more than 0.05% by weight, more preferably no more than 0.01% by weight, more preferably no more than 0.005% by weight, more preferably no more than 0.001% by weight, more preferably no more than 0.0005% by weight, and more preferably no more than 0.0001% by weight.

[0066] 7. The zeolitic material comprises one or more metal cations in the ion-exchange sites of the zeolitic framework, the one or more metal cations being selected from the group consisting of alkaline earth metals and rare earth metals including mixtures of two or more thereof, preferably from the group consisting of Mg, Ca, Sr, Sc, Y, La, Ce, Pr, Nd and mixtures of two or more thereof, more preferably from the group consisting of Mg, Ca, La, Ce and mixtures of two or more thereof, more preferably the zeolitic material comprises Mg and / or La in the ion-exchange sites of the zeolitic framework, more preferably the zeolitic material comprises one or more zeolites selected from the group consisting of Mg-ZSM-5, La-ZSM-5, La-mordenite, and mixtures of two or three thereof, more preferably La-ZSM-5 and / or La-mordenite; more preferably the zeolitic material is composed of one or more zeolites selected from the group consisting of Mg-ZSM-5, La-ZSM-5, La-mordenite, and mixtures of two or three thereof, more preferably the zeolitic material is La-ZSM-5 and / or La-mordenite.

[0067] 8. The method according to any one of the preceding embodiments, wherein Y is selected from the group consisting of Si, Sn, Ti, Zr, Ge, and mixtures of two or more thereof, preferably from the group consisting of Si, Sn, Ti, and mixtures of two or more thereof, Y preferably comprises Si or both Si and Sn, more preferably Y comprises Si, more preferably Y is either Si or both Si and Sn, more preferably Y is Si, more preferably the zeolitic material comprises a zeolite beta having a framework comprising Si and Sn as tetravalent elements, more preferably a zeolite beta having a framework comprising Si and Sn as tetravalent elements, more preferably the zeolitic material is composed of a zeolite beta having a framework comprising Si and Sn as tetravalent elements, more preferably a zeolite beta having a framework comprising Si and Sn as tetravalent elements.

[0068] 9. The method according to any one of the preceding embodiments, wherein the framework structure of the zeolitic material further comprises X2O3, where X represents one or more trivalent elements, X being selected from the group consisting of Al, B, In, Ga, and mixtures of two or more thereof, and X preferably comprises Al, more preferably X is Al.

[0069] 10. The method according to embodiment 9, wherein the zeolitic material exhibits a molar ratio of YO2:X2O3 in the range of 2-300, preferably 6-200, more preferably 8-150, more preferably 10-100, more preferably 15-80, more preferably 20-70, more preferably 40-60, and more preferably 45-55.

[0070] 11. The method of embodiment 9 or 110, wherein the zeolitic material comprises ZSM-5, preferably the zeolitic material is ZSM-5.

[0071] 12. The zeolite material contained in the catalyst has a total amount of acid sites in the range of 0.4 to 4 mmol / g, preferably 0.5 to 3 mmol / g, more preferably 0.6 to 2.8 mmol / g, more preferably 0.8 to 2.6 mmol / g, more preferably 1 to 2.4 mmol / g, more preferably 1.2 to 2.2 mmol / g, more preferably 1.4 to 2 mmol / g, more preferably 1.6 to 1.9 mmol / g, and more preferably 1.7 to 1.8 mmol / g; 12. The method according to any one of the preceding claims, wherein the total amount of acid sites is defined as the total amount of moles of ammonia desorbed per mass of the zeolitic material as measured by temperature programmed desorption of ammonia (NH3-TPD).

[0072] 13. The method according to embodiment 12, wherein the total amount of acid sites is defined as the amount of ammonia desorbed per mass of the zeolitic material as measured by temperature programmed desorption of ammonia (NH3-TPD) in the temperature range of 150 to 750°C, preferably 180 to 680°C, more preferably 190 to 630°C, more preferably 200 to 600°C, more preferably 205 to 570°C, more preferably 210 to 540°C, more preferably 215 to 490°C, and more preferably 220 to 440°C.

[0073] 14. The method according to any one of the preceding embodiments 1 to 13, wherein the zeolite material contained in the catalyst has a certain amount of medium acid sites, the amount of medium acid sites being in the range of 0.4 to 4 mmol / g, preferably 0.5 to 3 mmol / g, more preferably 0.6 to 2.8 mmol / g, more preferably 0.8 to 2.6 mmol / g, more preferably 1 to 2.4 mmol / g, more preferably 1.2 to 2.2 mmol / g, more preferably 1.4 to 2 mmol / g, more preferably 1.6 to 1.9 mmol / g, and more preferably 1.7 to 1.8 mmol / g.

[0074] 15. The method according to embodiment 14, wherein the amount of intermediate acid sites is defined as the amount of ammonia desorbed per mass of the zeolitic material as measured by temperature programmed desorption of ammonia (NH3-TPD) in the temperature range of 150 to 400°C, preferably 180 to 320°C, more preferably 190 to 280°C, more preferably 200 to 250°C, more preferably 205 to 240°C, more preferably 210 to 230°C, and more preferably 215 to 220°C.

[0075] 16. The method according to any one of the preceding embodiments, wherein the zeolite material contained in the catalyst has strong acid sites less than 1 mmol / g, preferably less than 0.5 mmol / g, more preferably less than 0.2 mmol / g, more preferably less than 0.1 mmol / g, more preferably less than 0.05 mmol / g, more preferably less than 0.03 mmol / g, more preferably less than 0.02 mmol / g, more preferably less than 0.01 mmol / g, more preferably less than 0.005 mmol / g, and more preferably less than 0.001 mmol / g.

[0076] 17. The method according to embodiment 16, wherein the amount of strong acid sites is defined as the amount of ammonia desorbed per mass of the zeolitic material measured by temperature programmed desorption of ammonia (NH3-TPD) in the temperature range of 300 to 750°C, preferably 400 to 720°C, more preferably 450 to 690°C, more preferably 500 to 670°C, more preferably 530 to 650°C, more preferably 550 to 630°C, more preferably 570 to 610°C, and more preferably 590 to 600°C.

[0077] 18. The one or more alkenes provided in (1) are represented by the formula (I): [ka] (wherein R and R' are alkyl groups). 18. The method of any one of the preceding embodiments, comprising one or more alkenes according to the formula:

[0078] 19. The dimerization product or products of the alkenes obtained in (2) are represented by the formula (II): [ka] (wherein R and R' are alkyl groups). 19. The method of any one of the preceding embodiments, comprising one or more alkenes according to the formula:

[0079] 20. The method according to embodiment 18 or 19, wherein R and R' are, independently of each other, optionally branched and / or optionally substituted and / or optionally unsaturated C1-C6 alkyl groups, preferably C1-C5 alkyl groups, more preferably C1-C4 alkyl groups, more preferably C1-C3 alkyl groups, more preferably C1-C2 alkyl groups, and more preferably C1 alkyl groups, which may be optionally branched and / or optionally substituted and / or optionally unsaturated; more preferably R and R' are, independently of each other, selected from the group consisting of optionally substituted methyl, ethyl, propyl, butyl, pentyl and hexyl, more preferably from the group consisting of optionally substituted methyl, ethyl, propyl, butyl and pentyl, more preferably from the group consisting of optionally substituted methyl, ethyl, propyl and butyl, more preferably from the group consisting of optionally substituted methyl, ethyl and propyl; more preferably R and R' are, independently of each other, optionally substituted methyl or ethyl, preferably methyl.

[0080] 21. The one or more alkenes provided in (1) are selected from the group consisting of optionally substituted isobutene, 2-methyl-1-butene, 2-ethyl-1-butene, 2-methyl-1-pentene, 2-ethyl-1-pentene, 2-n-propyl-1-pentene, 2,3-dimethyl-1-butene, 2-ethyl-3-methyl-1-butene, 2-i-propyl-1-pentene, 2-i-propyl-3-methyl-1-butene, and mixtures of two or more thereof, more preferably optionally substituted isobutene, 2-methyl-1-butene, 2-ethyl-1-butene, 2-methyl-1-pentene, 2-ethyl-1-pentene, 2,3- The process according to any one of the preceding embodiments, comprising one or more alkenes selected from the group consisting of optionally substituted isobutene, 2-methyl-1-butene, 2-ethyl-1-butene, 2-methyl-1-pentene, 2,3-dimethyl-1-butene, and mixtures of two or more thereof, more preferably selected from the group consisting of optionally substituted isobutene, 2-methyl-1-butene, 2-ethyl-1-butene, 2-methyl-1-pentene, 2,3-dimethyl-1-butene, and mixtures of two or more thereof, more preferably the alkene of formula (II) is optionally substituted isobutene and / or 2-methyl-1-butene, preferably isobutene or 2-methyl-1-butene and more preferably isobutene.

[0081] 22. The one or more dimerization products obtained in (2) are one or more alkanes and / or one or more alkenes, preferably one or more alkenes, more preferably one or more C4 to C20 alkenes, more preferably one or more C4 to C16 alkenes, more preferably one or more C5 to C14 alkenes, more preferably one or more C5 to C13 alkenes, more preferably one or more C6 to C12 alkenes, more preferably one or more C6 to C11 alkenes, more preferably one or more C7 to C10 alkenes, more preferably one or more C7 to C18 alkenes, more preferably one or more C8 to C19 alkenes, more preferably one or more C9 to C11 alkenes, more preferably one or more C10 to C12 alkenes, more preferably one or more C11 to C13 alkenes, more preferably one or more C12 to C13 alkenes, more preferably one or more C13 to C14 alkenes, more preferably one or more C14 to C16 ... 22. The process according to any one of the preceding embodiments, wherein the one or more dimerization products obtained in (2) comprise one or more alkenes selected from the group consisting of 1-octene, 2,4,4-trimethyl-1-pentene, 2,4,4-trimethyl-2-pentene, and mixtures of two or three thereof, more preferably wherein the one or more dimerization products obtained in (2) comprise 1-octene and / or 2,4,4-trimethyl-1-pentene, more preferably 2,4,4-trimethyl-1-pentene.

[0082] 23. The method according to any one of the preceding embodiments, wherein the content of the one or more alkenes in the gas stream provided in (1) and contacted with the catalyst in (2) is in the range of 5 to 100% by volume, preferably in the range of 10 to 99% by volume, more preferably in the range of 15 to 98% by volume, more preferably in the range of 20 to 95% by volume, more preferably in the range of 25 to 90% by volume, more preferably in the range of 30 to 80% by volume, more preferably in the range of 35 to 70% by volume, more preferably in the range of 40 to 60% by volume, and more preferably in the range of 45 to 55% by volume, based on the total volume of the gas stream.

[0083] 24. The method of any one of embodiments 1-23, wherein the gas stream provided in (1) and contacted with the catalyst in (2) contains no more than 50 vol.%, preferably no more than 30 vol.%, more preferably no more than 20 vol.%, more preferably no more than 10 vol.%, more preferably no more than 5 vol.%, more preferably no more than 3 vol.%, more preferably no more than 2 vol.%, more preferably no more than 1 vol.%, more preferably no more than 0.5 vol.%, more preferably no more than 0.1 vol.%, more preferably no more than 0.05 vol.%, more preferably no more than 0.01 vol.%, more preferably no more than 0.005 vol.%, and more preferably no more than 0.001 vol.% aliphatic organic compounds based on the total volume of the gas stream.

[0084] 25. The method of embodiment 24, wherein the one or more aliphatic organic compounds are selected from the group consisting of optionally substituted and / or optionally cyclic and / or optionally branched (C2-C20) hydrocarbons and mixtures of two or more thereof, preferably (C2-C16) hydrocarbons, more preferably (C2-C16) hydrocarbons, more preferably (C2-C14) hydrocarbons, more preferably (C2-C12) hydrocarbons, more preferably (C2-C10) hydrocarbons, more preferably (C2-C8) hydrocarbons, more preferably (C2-C6) hydrocarbons, more preferably (C3-C5) hydrocarbons, and more preferably C4 hydrocarbons, and mixtures thereof.

[0085] 26. One or more optionally substituted and / or optionally cyclic hydrocarbons are branched, preferably the one or more branched hydrocarbons are of the formula: [ka] (In the formula, R 1 , R 2 , and R 3are each independently an optionally substituted and / or optionally cyclic and / or optionally branched (C1-C8) alkyl, preferably a (C1-C6) alkyl, more preferably a (C1-C5) alkyl, more preferably R 1 , R 2 , and R 3 are each independently an optionally substituted and / or optionally branched (C1-C4) alkyl, preferably a (C1-C3) alkyl, more preferably R 1 , R 2 , and R 3 are each independently optionally substituted methyl or ethyl, preferably optionally substituted methyl. 26. The method of embodiment 25, comprising:

[0086] 27. One or more aliphatic organic compounds are substituted with one or more functional groups, the one or more functional groups being selected from the group consisting of hydroxyl, halogen, carbonyl, aldehyde, carbonate, carboxylate, carboxyl, ester, ether, carboxamide, amine, imine, cyanate, isocyanate, nitrate, nitrile, isonitrile, sulfide, sulfinyl, sulfonyl, sulfino, sulfo, thiocyanate, isothiocyanate, phosphino, phosphono, and phosphate; More preferably, from the group consisting of hydroxyl, halogen, carbonyl, aldehyde, carboxylate, carboxyl, ester, ether, carboxamide, amine, imine, cyanate, isocyanate, nitrate, nitrile, isonitrile, and combinations of two or more thereof, More preferably, from the group consisting of hydroxyl, halogen, carbonyl, aldehyde, carboxylate, carboxyl, ester, ether, and combinations of two or more thereof, More preferably, from the group consisting of hydroxyl, halogen, carbonyl, alkoxy, and combinations of two or more thereof, More preferably, from the group consisting of hydroxyl, fluoro, chloro, bromo, (C1-C3)alkoxy, and combinations of two or more thereof, More preferably, from the group consisting of hydroxyl, fluoro, chloro, (C1-C2)alkoxy, and combinations of two or more thereof, More preferably, it is preferably selected from the group consisting of hydroxyl, fluoro, chloro, methoxy, and combinations of two or more thereof; The method of embodiment 25 or 26, wherein more preferably the one or more aliphatic compounds are substituted with one or more hydroxyl groups.

[0087] 28. The method of embodiment 25 or 26, wherein the one or more aliphatic organic compounds are unsubstituted hydrocarbons, preferably the one or more aliphatic organic compounds comprise isobutane, more preferably the one or more aliphatic organic compounds are isobutane.

[0088] 29. The method according to any one of the preceding embodiments, wherein the gas stream provided in (1) and contacted with the catalyst in (2) further comprises one or more inert gases, the one or more inert gases being selected from the group consisting of nitrogen, helium, argon, CO2, and mixtures of two or more thereof, preferably from the group consisting of nitrogen, argon, CO2, and mixtures of two or more thereof, more preferably the gas stream further comprises nitrogen and / or argon, more preferably nitrogen and argon.

[0089] 30. The method according to embodiment 29, wherein the content of one or more inert gases in the gas stream provided in (1) and contacted with the catalyst in (2) is in the range of 0 to 95% by volume, preferably in the range of 1 to 90% by volume, more preferably in the range of 2 to 85% by volume, more preferably in the range of 5 to 80% by volume, more preferably in the range of 10 to 75% by volume, more preferably in the range of 20 to 70% by volume, more preferably in the range of 30 to 65% by volume, more preferably in the range of 40 to 60% by volume, and more preferably in the range of 45 to 55% by volume, based on the total volume of the gas stream.

[0090] 31. The method according to any one of embodiments 1 to 30, wherein the contact in (2) is carried out at a temperature in the range of 80 to 350°C, more preferably 100 to 320°C, more preferably 120 to 300°C, more preferably 140 to 280°C, more preferably 160 to 260°C, more preferably 180 to 250°C, more preferably 200 to 245°C, more preferably 220 to 240°C, and more preferably 225 to 235°C.

[0091] 32. The method according to any one of the preceding embodiments 1 to 31, wherein the contacting in (2) is carried out at a pressure in the range of 2 to 80 bar, preferably 4 to 60 bar, more preferably 6 to 50 bar, more preferably 8 to 45 bar, more preferably 10 to 40 bar, more preferably 12 to 38 bar, more preferably 14 to 36 bar, more preferably 16 to 34 bar, more preferably 18 to 32 bar, more preferably 20 to 30 bar, more preferably 22 to 28 bar, and more preferably 24 to 26 bar.

[0092] 33. The method of any one of the preceding embodiments, wherein the contacting in (2) is carried out in a continuous and / or batchwise manner, preferably in a continuous manner.

[0093] 34. The contact in (2) is carried out in a continuous manner, and the space velocity of the contact in (2) is 10 to 10,000 h -1 , preferably 50 to 5,000 hours -1 , more preferably 100 to 3,000 hours -1 , more preferably 300 to 2,500 hours -1 , more preferably 500 to 1,800 hours -1 , more preferably 700 to 1,500 hours -1 , more preferably 800 to 1,200 hours -1 , more preferably 900 to 1,100 hours -1 34. The method of embodiment 33, wherein the range is

[0094] 35. The process according to embodiment 33 or 34, wherein the contacting in (2) is carried out in a continuous manner, and the catalyst life is in the range of 50 to 2,000 hours, preferably 100 to 1,000 hours, more preferably 150 to 500 hours, more preferably 200 to 400 hours, more preferably 230 to 350 hours, and more preferably 250 to 300 hours, during which the continuous process is carried out without interrupting the dimerization reaction.

[0095] 36. The method (3) separating one or more unreacted alkenes from the reaction mixture M1 obtained in (2) to obtain a mixture M2 containing one or more alkenes; (4) recycling the mixture M2 containing one or more alkenes to (1); 36. The method of any one of embodiments 1 to 35, further comprising:

[0096] 37. The method of any one of the preceding embodiments, wherein the catalyst is regenerated at regular intervals.

[0097] 38. The method of embodiment 37, wherein the regeneration is carried out by contacting the catalyst with a gas stream containing oxygen, the contacting being carried out at a temperature in the range of 250 to 1000°C, preferably 300 to 900°C, more preferably 350 to 800°C, more preferably 400 to 700°C, more preferably 450 to 650°C, and more preferably 500 to 600°C.

[0098] 39. The method of embodiment 37 or 38, wherein the regenerating gas stream contains oxygen in an amount of 0.1 to 25 vol.%, preferably 0.5 to 20 vol.%, more preferably 1 to 15 vol.%, more preferably 1.5 to 12 vol.%, more preferably 2 to 10 vol.%, more preferably 2.5 to 8 vol.%, more preferably 3 to 7 vol.%, more preferably 3.5 to 6 vol.%, and more preferably 4 to 5 vol.%, based on the total volume of the gas stream.

[0099] 40. The method according to any one of embodiments 37 to 39, wherein the regenerating gas stream further comprises one or more inert gases, the one or more inert gases being selected from the group consisting of nitrogen, helium, argon, CO2, and mixtures of two or more thereof, preferably from the group consisting of nitrogen, argon, CO2, and mixtures of two or more thereof, more preferably the gas stream further comprises nitrogen and / or argon, more preferably nitrogen and argon.

[0100] 41. The method according to any one of embodiments 37 to 40, wherein the content of the one or more inert gases in the regenerating gas stream is in the range of 75 to 99.9 vol.%, preferably in the range of 80 to 99.5 vol.%, more preferably in the range of 85 to 99 vol.%, more preferably in the range of 88 to 98.5 vol.%, more preferably in the range of 90 to 98 vol.%, more preferably in the range of 92 to 97.5 vol.%, more preferably in the range of 93 to 97 vol.%, more preferably in the range of 94 to 96.5 vol.%, and more preferably in the range of 95 to 96 vol.%, based on the total volume of the gas stream.

[0101] 42. A zeolite material having a BEA-type framework structure has at least the following reflectance: [Table 2] wherein 100% corresponds to the maximum peak intensity in the range of 20 to 45° 2θ in the X-ray powder diffraction pattern; 42. The method according to any one of the preceding embodiments, wherein the BEA-type framework structure comprises YO2 and X2O3, where Y is a tetravalent element and X is a trivalent element.

[0102] 43. The method according to embodiment 42, wherein the zeolitic material having a BEA-type framework structure exhibits a molar ratio of YO2:X2O3 in the range of 2 to 100, preferably 3 to 50, more preferably 4 to 30, more preferably 5 to 25, more preferably 6 to 20, more preferably 7 to 18, more preferably 8 to 16, and more preferably 9 to 14.

[0103] 44. The method of embodiment 42 or 43, wherein the zeolitic material comprises zeolite beta, preferably the zeolitic material is zeolite beta.

[0104] 45. The method according to any one of the preceding embodiments, wherein the zeolitic material having a BEA-type framework structure contained in the catalyst is obtainable and / or obtained by an organic template-free synthesis method.

[0105] 46. ​​An organic template-free synthesis method comprising: (A) preparing a mixture comprising one or more YO2 sources, one or more X2O3 sources, and seed crystals, the seed crystals comprising a material having a BEA-type framework structure; (B) crystallizing the mixture obtained in (A) to obtain a zeolitic material having a BEA-type framework structure; Including, Y is a tetravalent element and X is a trivalent element; 46. ​​The method of embodiment 45, wherein the mixture prepared in (A) and crystallized in (B) does not contain an organic template as a structure directing agent.

[0106] 47. The method according to embodiment 46, wherein the mixture prepared in (A) and crystallized in (B) contains no more than 5% by weight of carbon, calculated as the element and based on 100% by weight of Y contained in the mixture, preferably no more than 1% by weight, more preferably no more than 0.5% by weight, more preferably no more than 0.1% by weight, more preferably no more than 0.05% by weight, more preferably no more than 0.01% by weight, more preferably no more than 0.005% by weight, more preferably no more than 0.001% by weight, more preferably no more than 0.0005% by weight, and more preferably no more than 0.0001% by weight of carbon, calculated as the element and based on 100% by weight of Y contained in the mixture.

[0107] 48. The method according to embodiment 46 or 47, wherein the zeolitic material having a BEA-type framework structure obtained in (B) comprises one or more alkali metals AM, the AM being preferably selected from the group consisting of Li, Na, K, Cs, and combinations of two or more thereof, more preferably from the group consisting of Li, Na, K, and combinations of two or more thereof, more preferably the alkali metal AM is Na and / or K, more preferably Na.

[0108] 49. The method of embodiment 48, wherein the molar ratio of AM:YO2 in the mixture prepared in (A) and crystallized in (B) is in the range of 0.05 to 5, preferably 0.1 to 2, more preferably 0.3 to 1, more preferably 0.4 to 0.8, more preferably 0.45 to 0.7, more preferably 0.5 to 0.65, and more preferably 0.55 to 0.6.

[0109] 50. The method of any one of embodiments 46-49, wherein Y is selected from the group consisting of Si, Sn, Ti, Zr, Ge, and mixtures of two or more thereof, and Y is preferably Si.

[0110] 51. The method according to any one of embodiments 46 to 50, wherein the one or more YO2 sources contained in the mixture prepared in (A) and crystallized in (B) comprise one or more silicates, preferably one or more alkali metal silicates, wherein the alkali metal is preferably selected from the group consisting of Li, Na, K, Rb, and Cs, more preferably the alkali metal is Na and / or K, more preferably the alkali metal is Na, more preferably the one or more YO2 sources contained in the mixture prepared in (A) and crystallized in (B) comprise water glass, preferably sodium silicate and / or potassium silicate, more preferably sodium silicate.

[0111] 52. The method of embodiment 51, wherein the one or more YO2 sources contained in the mixture prepared in (A) and crystallized in (B) further comprise one or more silicas, preferably one or more silica hydrosols and / or one or more colloidal silicas, and more preferably one or more colloidal silicas.

[0112] 53. The method of any one of embodiments 46-52, wherein X is selected from the group consisting of Al, B, In, Ga, and mixtures of two or more thereof, and X is preferably Al.

[0113] 54. The method according to any one of embodiments 46 to 53, wherein the one or more X2O3 sources contained in the mixture prepared in (A) and crystallized in (B) comprise one or more aluminates, preferably alkali metal aluminates, the alkali metal being preferably selected from the group consisting of Li, Na, K, Rb, and Cs, more preferably the alkali metal is Na and / or K, more preferably the alkali metal is Na.

[0114] 55. The method according to any one of embodiments 46 to 54, wherein the molar ratio of YO2:X2O3 of the mixture prepared in (A) and crystallized in (B) is in the range of 1 to 200, preferably 5 to 100, more preferably 10 to 50, more preferably 15 to 40, more preferably 20 to 30, more preferably 23 to 25, and more preferably 23.5 to 24.

[0115] 56. The method according to any one of embodiments 46 to 55, wherein the amount of seed crystals contained in the mixture prepared in (A) and crystallized in (B) is in the range of 0.5 to 30% by weight, preferably 1 to 25% by weight, more preferably 3 to 20% by weight, more preferably 5 to 15% by weight, more preferably 8 to 12% by weight, and more preferably 9 to 11% by weight, calculated as YO2, based on 100% by weight of one or more YO2 sources in the mixture.

[0116] 57. The method according to any one of embodiments 46 to 56, wherein the mixture prepared in (A) and crystallized in (B) further comprises one or more solvents, said one or more solvents preferably comprising water, more preferably deionized water, more preferably water, preferably deionized water, is used as the solvent further comprised in the mixture prepared in (A) and crystallized in (B).

[0117] 58. The method of embodiment 57, wherein the molar ratio of H2O:YO2 of the mixture prepared in (A) and crystallized in (B) is in the range of 5 to 100, preferably 10 to 50, more preferably 13 to 30, more preferably 15 to 20, and more preferably 17 to 18.

[0118] 59. The method of any one of embodiments 46 to 58, wherein the crystallization in (B) comprises heating the mixture at a temperature in the range of preferably 80 to 200°C, more preferably 90 to 180°C, more preferably 100 to 160°C, more preferably 110 to 140°C, and more preferably 115 to 130°C.

[0119] 60. The method according to any one of embodiments 46 to 59, wherein the crystallization in (B) is carried out under autogenous pressure, preferably under solvothermal conditions and more preferably under hydrothermal conditions.

[0120] 61. The method of embodiment 59 or 60, wherein in (B) the mixture is heated for a period in the range of 5 to 200 hours, preferably 20 to 150 hours, more preferably 50 to 100 hours, and more preferably 65 to 75 hours.

[0121] 62. An organic template-free synthesis method for the preparation of zeolitic materials having a BEA-type framework structure, comprising: (C) isolating the zeolitic material having a BEA-type framework structure obtained in (B), preferably by filtration; and (D) optionally washing the zeolitic material with a BEA-type framework structure obtained in (B) or (C), preferably in (C); and / or (E) Optionally, drying the zeolitic material having a BEA-type framework structure obtained in (B), (C) or (D), preferably in (D). Further comprising: Steps (C) and / or (D) and / or (E) may be performed in any order; One or more of the above steps are preferably repeated one or more times. The method according to any one of embodiments 46 to 61.

[0122] 63. An organic template-free synthesis method for the preparation of zeolitic materials having a BEA-type framework structure, comprising: (F) Removing one or more of the ionic non-framework elements contained in the zeolitic material having a BEA-type framework structure obtained in (C), (D) or (E), preferably (E), from the zeolitic material by H + and / or NH4 + , preferably NH4 + and / or preferably and (G) drying and / or calcining the zeolitic material having a BEA-type framework structure obtained in (C), (D), (E) or (F), preferably drying and calcining. 63. The method of embodiment 62, further comprising: EXAMPLES

[0123] <Acid point measurement>: Temperature programmed desorption of ammonia (NH3-TPD) Temperature programmed desorption of ammonia (NH3-TPD) was performed on an automatic chemisorption analyzer (Micromeritics AutoChem II 2920) with a thermal conductivity detector. Continuous analysis of the desorbed species was performed with an online mass spectrometer (Pfeiffer Vacuum OmniStar QMG200). Samples (0.1 g) were introduced into a quartz tube and analyzed using the program described below. The temperature was measured by a Ni / Cr / Ni thermocouple directly above the sample in the quartz tube. He with a purity of 5.0 was used for the analysis. A blank sample was analyzed for calibration before every measurement.

[0124] 1. Preparation: Start recording; measure once per second. 25°C and He flow rate 30 cm 3 Wait 10 min at room temperature (approximately 25 °C and 1 atm) and then heat up to 600 °C at a heating rate of 20 K / min and hold for 10 min. He flow (30 cm 3 / min) to 100 °C (furnace gradient temperature) at a cooling rate of 20 K / min, and then cooled to 100 °C under a He flow (30 cm 3 / min) at a cooling rate of 3 K / min to 100°C (sample gradient temperature). 2. Saturation with NH3: Start of recording; one measurement per second. The gas flow was changed to a mixture of 10% NH3 in He at 100 °C (75 cm 3 / min; 100° C. and 1 atm) and held for 30 minutes. 3. Excess removal: Start recording; measure once per second. Gas flow is increased to 75 cm at 100°C. 3 Change to He flow at 100° C. / min (100° C. and 1 atm) and hold for 60 min. 4.NH3-TPD: Start recording; measure once per second. He flow (flow rate: 30 cm 3 / min), heated to 600 °C at a heating rate of 10 K / min and held for 30 min. 5. Measurement completed.

[0125] The desorbed ammonia was measured by an online mass spectrometer and the signal from the thermal conductivity detector was shown to be generated by the desorbed ammonia. This involved monitoring the desorption of ammonia using the m / z=16 signal from ammonia. The amount of ammonia adsorbed (mmol / g sample) was determined by Micromeritics software via integration of the TPD signal with a horizontal baseline.

[0126] <Reference Example 1>: Synthesis of zeolite beta (H type) from organic template-free synthesis 12.693 kg of distilled water was charged to a 60 L autoclave. Two portions of 477.5 g of NaAlO2 (available from Aldrich) were dissolved in 2.5 L of distilled water each and added to the autoclave, where 3.5 L of distilled water was used for rinsing between each step. 21.447 kg of a sodium water glass solution (26% by weight SiO2 and 8% by weight Na2O; available from Woellner) were gradually added with stirring at 200 rpm, followed by 3.762 kg of colloidal silica (Ludox® AS40 from Grace) and the resulting mixture was stirred at 200 rpm for another 2 hours. Then, 717 g of zeolite beta seeds (commercially available under the trade name CP814C from Zeolyst International, Valley Forge, PA19482, USA, which was converted to H-form by calcination) were added in small portions to the mixture, thus obtaining an aluminosilicate gel with a molar ratio of 1.00 SiO2:0.042 Al2O3:0.29 Na2O:17.49 H2O. The reaction mixture was then crystallized in an autoclave with stirring at 100 rpm, the mixture was heated to 120°C within 3 hours and the temperature was maintained for 67 hours. The solid reaction product was then filtered off, washed and made electrically neutral (conductivity of the wash water <200 μS). The solid was dried overnight in a drying oven at 120°C, obtaining 1.9 kg of a white powder of zeolite beta, which showed a crystallinity of 71% as measured by X-ray diffraction.

[0127] Then, 302 g of the resulting zeolite beta and 301 g of ammonium nitrate were added to 2 kg of distilled water and stirred. The suspension was then transferred to a 4 L round bottom flask and the first vessel was rinsed with 1 L of distilled water. The resulting mixture was then heated to 80° C. and maintained at this temperature with continuous stirring for 2 hours. The solids were filtered off and the filter cake was then dried at 120° C. for 3 hours and then calcined at 450° C. for 5 hours to obtain 270 g of ion-exchanged zeolite beta.

[0128] Then, 267 g of the zeolite beta product from the first ion-exchange step and 265.3 g of ammonium nitrate were placed in a 5 L beaker and suspended in 2 kg of distilled water. The suspension was then transferred to a 4 L round bottom flask and the first vessel was rinsed with 650 mL of distilled water. The resulting mixture was then heated to 80° C. and maintained at this temperature with continuous stirring for 2 hours. The solids were filtered off and the filter cake was then dried at 120° C. for 3 hours and then calcined at 450° C. for 5 hours to obtain 234.2 g of ion-exchanged zeolite beta.

[0129] Then, 233.4 g of the zeolite beta product from the second ion exchange step and 233 g of ammonium nitrate were placed in a 5 L beaker and suspended in 1.8 kg of distilled water. The suspension was then transferred to a 4 L round bottom flask and the first vessel was rinsed with 550 mL of distilled water. The resulting mixture was then heated to 80° C. and maintained at this temperature with continuous stirring for 2 hours. The solids were filtered off and the filter cake was then dried at 120° C. for 3 hours and then calcined at 450° C. for 5 hours to obtain zeolite beta in its H form.

[0130] Elemental analysis of the product obtained: 4.9% by weight Al, 0.05% by weight Na, and 34% by weight Si.

[0131] <Reference Example 2>: Synthesis of ZSM-5 2 m 3Into the reactor, 79.61 kg of distilled water are initially introduced. 411.15 kg of aqueous tetrapropylammonium hydroxide solution (TPAOH; 40% by weight) are added to the water with stirring (70 rpm). The suspension is left to stir for another 10 minutes. 8.2 kg of solid NaOH are gradually added in 2.5 kg portions with stirring, the system being mixed for 5 minutes after each portion. Then, 29.25 kg of aluminum triisopropoxide are added to the suspension and the system is stirred for another hour. Finally, 538.19 kg of colloidal silica (Ludox AS-40) are added, followed by an additional 10 kg of distilled water. After the synthesis mixture is stirred for another hour at room temperature, the reactor is flushed with nitrogen gas and the pressure is reduced to ~900 mbar. The reactor is then heated to 170 °C in 11 hours. The hydrothermal synthesis is carried out at 170 °C with stirring at 70 rpm for 72 hours. After crystallization, the synthesis mixture is cooled to 30° C. The suspension is transferred to a larger vessel where the pH of the suspension is adjusted to 7±0.5 by adding 10% by weight aqueous nitric acid solution. The pH adjusted suspension is left stirring at 70 rpm for a further 30 min. The zeolite is separated by filtration and the filter cake is washed with distilled water until the conductivity of the wash water is <200 μS. The filter cake is then dried at 120° C. for 96 h. The dried material is calcined in air at 550° C. for 6 h to obtain a BET surface area of ​​390 m 2 A calcined ZSM-5 zeolite having a crystallinity of 94% was obtained, as determined by X-ray diffraction, with a molecular weight of 1.01 / g.

[0132] 250 kg of distilled water are added to a 400 L reactor and 25 kg of ammonium nitrate are added under stirring (150 rpm). The suspension is heated to 80°C and then 25 kg of calcined zeolite are added. The mixture is stirred at 80°C for another hour. The reaction mixture is then cooled, filtered off using a filter press and washed with water until the conductivity of the wash water is <200 μS. The ion-exchange process is then repeated to obtain ammonium exchanged ZSM-5. The filter cake obtained after the second ammonium ion-exchange process is dried at 120°C for 10 hours and calcined in air at 500°C for 5 hours (heating rate 2°C / min) to obtain the H-form of ZSM-5.

[0133] Elemental analysis showed that the product obtained had a content of <0.1 g carbon, 1.6 g aluminum, <0.01 g sodium and 43 g silicon measured per 100 g of material.

[0134] The BET surface area is 408 m 2 It was measured to be.

[0135] <Reference Example 3>: Measurement of acid sites The acid sites and total amount of the zeolitic materials from Examples 1 and 2, as well as mordenite (CBV 21A, commercially available from Zeolyst) and zeolite beta (CP814E, commercially available from Zeolyst) were measured by temperature programmed desorption of ammonia. The results are shown in Table 1 below. The desorption peaks can be classified as corresponding to weak acid sites (peak maximum temperature <200° C.), medium acid sites (peak maximum temperature <200-400° C.) and strong acid sites (peak maximum temperature >400° C.).

[0136] [Table 3]

[0137] Example 3: Catalyst test The catalyst from Example 1 and further catalysts were tested in the dimerization of isobutene at different temperatures and pressures (50% by volume of gas feed). The gas space velocity for all reactions was 1,000 h -1whereby each catalyst was activated overnight with an inert gas flow (90% by volume N2 and 10% by volume Ar) prior to reaction. Further catalysts tested were mordenite (CBV 21A, commercially available from Zeolyst), Y zeolite (CBV-600 and CBV-300, each commercially available from Zeolyst), and zeolite beta (CP 814E, commercially available from Zeolyst). All further catalysts tested were calcined at 500°C for 5 hours each and then tested for conversion of the commercial ammonium form to the respective H form. The test results are shown in Tables 2 and 3 below, where the C8 alkenes detected in the products produced in the reaction were 1-octene, 2,4,4-trimethyl-1-pentene, and 2,4,4-trimethyl-2-pentene. The results in Table 1 represent average values ​​of the reaction selectivities for C8 alkenes, non-C8 alkanes, and alkenes, and aromatics for a 19-hour period on the gas stream, except for Reference Example 1, which represents an average value for a 20-hour period on the gas stream.

[0138] [Table 4]

[0139] The results in Table 3 show average values ​​of conversion and catalyst deactivation rate for 19 hours on gas stream, except for Reference Example 1 which again shows average values ​​for 20 hours on gas stream.

[0140] [Table 5]

[0141] As can be interpreted from the results shown in Tables 1 and 2, it has surprisingly been found that a process for the dimerization of alkenes that gives high selectivity to dimerization products, especially to highly branched dimerization products, can be provided by using certain zeolitic materials as catalysts. It has further been unexpectedly found that not only does the use of zeolitic materials make it possible to maintain the dimerization reaction at high alkene conversions over long reaction times, but that the zeolitic materials can be easily regenerated and provide performance comparable to that of virgin catalysts even after regeneration cycles.

Claims

1. 1. A process for dimerizing an alkene comprising the steps of: (1) providing a gas stream comprising one or more alkenes; (2) contacting the gas stream provided in (1) with a catalyst to obtain a mixture M1 comprising one or more dimerization products of one or more alkenes; Including, (2) The catalyst in accordance with (1) above comprises a zeolitic material having a framework structure type selected from the group consisting of MOR, BEA, FER, MFI, TON, FAU, and mixtures of two or more thereof; The framework structure of the zeolite material is YO 2 wherein Y represents one or more tetravalent elements; method.

2. 2. The method of claim 1, wherein Y represents one or more tetravalent elements, Y being selected from the group consisting of Si, Sn, Ti, Zr, Ge, and mixtures of two or more thereof.

3. The framework structure of the zeolite material is X 2 O 3 3. The method of claim 1 or 2, further comprising: X represents one or more trivalent elements, X being selected from the group consisting of Al, B, In, Ga, and mixtures of two or more thereof.

4. The zeolite material contained in the catalyst has a total amount of acid sites in the range of 0.4 to 4 mmol / g; 4. The method according to any one of claims 1 to 3, wherein the total amount of acid sites is defined as the total molar amount of ammonia desorbed per mass of zeolitic material, as measured by temperature programmed desorption of ammonia (NH3-TPD).

5. The one or more alkenes provided in (1) are represented by the formula (I): 【Chemistry 1】 (wherein R and R' are alkyl groups).

5. The process according to claim 1 , comprising one or more alkenes according to

6. The dimerization product or products of the alkenes obtained in (2) are represented by the formula (II): 【Chemistry 2】 (wherein R and R' are alkyl groups).

6. The process according to claim 1 , comprising one or more alkenes according to

7. 7. The method according to claim 5 or 6, wherein R and R', independently of each other, are optionally branched and / or optionally substituted and / or optionally unsaturated alkyl groups selected from the group consisting of C1 to C6 alkyl groups, which may be optionally branched and / or optionally substituted and / or optionally unsaturated.

8. 8. The process of claim 1, wherein the gas stream provided in (1) and contacted with the catalyst in (2) contains no more than 50 volume percent aliphatic organic compounds, based on the total volume of the gas stream.

9. The method according to any one of claims 1 to 8, wherein the contacting in (2) is carried out at a temperature in the range of 80 to 350°C.

10. The method according to any one of claims 1 to 9, wherein the contacting in (2) is carried out at a pressure in the range of 2 to 80 bar.

11. The method of any one of claims 1 to 10, wherein the contacting in (2) is carried out in a continuous and / or batchwise manner.

12. (3) separating one or more unreacted alkenes from the reaction mixture M1 obtained in (2) to obtain a mixture M2 containing one or more alkenes; (4) recycling the mixture M2 containing one or more alkenes to (1); The method of claim 1 , further comprising:

13. 13. The process according to any one of claims 1 to 12, wherein the catalyst is regenerated at regular intervals.

14. The zeolitic material having a BEA-type framework structure has at least the following reflectance: 【Table 1】 wherein 100% is associated with the maximum peak intensity within the 20-45° 2θ range of the X-ray powder diffraction pattern; The BEA-type skeleton structure is YO 2 and X 2 O 3 14. The method of claim 1, wherein Y is a tetravalent element and X is a trivalent element.

15. 15. The process according to any one of claims 1 to 14, wherein the zeolitic material with a BEA-type framework structure comprised in the catalyst is obtainable and / or obtained by an organotemplate-free synthesis method.